Hellenistic and Roman terracottas - Papantoniou, Giorgos,; Michaēlidēs, Dēmētrēs,; Dikomitou-Eliadou, Maria, (Monumenta Graeca et Romana, 2019)
Edited by G. Papantoniou, D. Michaelides and M. Dikomitou-Eliadou, Hellenistic and Roman Terracottas is a collection of 29 chapters with an introduction presenting diverse and innovative approaches (archaeological, stylistic, iconographic, functional, contextual, digital, and physicochemical) in the study of ancient terracottas across the Mediterranean and the Near East, from the Hellenistic period to Late Antiquity. The 34 authors advocate collectively the significance of a holistic approach to the study of coroplastic art, which considers terracottas not simply as works of art but, most importantly, as integral components of ancient material culture. The volume will prove to be an invaluable companion to all those interested in ancient terracottas and their associated iconography and technology, as well as in ancient artefacts and classical archaeology in general.